Management of Palembang Care Program through House Repair Assistance According to Islamic Economics at BAZNAS Palembang City - Mutiara Muslimah; Oki Sapitri Menghayati (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
The Palembang Care Program is a social assistance program from the Palembang City National Amil Zakat Agency (BAZNAS) which aims to improve the quality of life of poor people, one of which is through house renovation assistance. This program is based on the principles of Islamic economics, namely piety, justice, humanity and curiosity. This research aims to analyze the Palembang Cares management program through house renovation assistance according to Islamic economics at BAZNAS Palembang City. This research uses a qualitative method with a descriptive approach. Data sources were obtained through interviews, observation and documentation. The research results show that the Pa-lembang Peduli management program through house renovation assistance at BAZNAS Palembang City is in accordance with Islamic economic principles. This can be seen from the beneficiary selection process which is carried out in a transparent and accountable manner, as well as the implementation of house construction which is carried out with attention to quality and environmental sustainability. To improve the quality of assistance for the Palembang Cares management program through better house renovations, BAZNAS Palembang City can carry out: 1) Mapping the target recipients of assistance; 2) Introduce the program and promote the program through social media, so that recipients of the Palembang program care are more targeted and the institution gains the trust of the community